BAHAN AJAR E-BOOK PENDIDIKAN AGAMA ISLAM: STUDI PADA SEKOLAH MENENGAH PERTAMA NEGERI 1 MUARA TELANG - Zainal Arifin; Abdurrahmansyah Abdurrahmansyah; Ahmad Zainuri; Ari Sandi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2020)
This research is motivated because there is a problem that there are many students whose interest in learning is lacking, especially for textual learning. Students prefer to learn instantaneously using internet facilities. done by the teacher. Whereas on the other hand, there is a problem of students not daring to express their opinions in class because of the lack of knowledge of the students themselves. This research uses qualitative methods. data using observation, interviews, and documentation. Data analysis uses qualitative data analysis techniques. The results showed that the implementation of e-books in PAI learning at SMP Negeri 1 Muara Telang ran smoothly because it was supported by communication and interaction factors between individual students and teachers well established, the characteristics of teachers and students who had the ability to use e-books, attitudes and the mindset of the teacher and students to work together towards progress together and the financial situation of parents who support, the good habits of parents, students and the environment from the socio-cultural aspects and a conducive school climate cooperate with each other for school progress. The obstacles in implementation are the unprepared attitude of students and the state of equipment that is not supportive.